The Relationship of Pregnant Woman’s Knowledge About Anemia With Compliance Consuming Iron (Fe) Tablets - Goretik, Maria; Nazarius, Yustina Riki; Romina, Fransiska (Universitas STRADA Indonesia, 2021)
Background Anemia in pregnancy is known to be a potential hazard to both mother and baby. The prevalence of iron deficiency anemia in Indonesian pregnant women is 50.5%. In West Kalimantan from 2014 to 2016 there was an increase in anemia reaching 5.74%. Knowledge is one of the factors in the formation of health behavior. Pregnant women are given iron (fe) added tablets every day during pregnancy or at least 90 tablets. Purpose The purpose of this study was to analyze the factors associated with the incidence of anemia in the Tanjung Hulu Public Health Center, Pontianak City in 2021. Methods This study used a descriptive analytic research design with a cross sectional design approach with a sample of 30 respondents. Result Based on the univariate analysis, it was found that 12 (40%) pregnant women had good knowledge and 12 (40%) pregnant women had sufficient knowledge and only 6 people (20%) had less knowledge about anemia. A total of 26 (86.7%) were obedient in consuming Fe tablets and only 4 (13.3%) pregnant women were not compliant in taking FE tablets. The results of bivariate analysis with rank spaerment correlation found that the significance value of Sig. (2-tailed) is 0.008. Conclusion There is a relationship between the level of knowledge of pregnant women about anemia with adherence to taking FE tablets